Efficacy of Herbicide Active Ingredients against Aquatic Weeds - Stephen F. Enloe; Ben Sperry; James Leary; Jay Ferrell (EDIS)
This publication answers some common questions and provides efficacy information for all herbicide active ingredients labeled for aquatic use in Florida. Written by Stephen F. Enloe, Ben Sperry, and James Leary, and published by the UF/IFAS Agronomy Department, revised May 2022.